2012
DOI: 10.1159/000337682
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Extracranial Internal Carotid Artery Tortuosity Index and Intraprocedural Complications during Carotid Artery Stenting

Abstract: Background: To investigate the correlation between tortuosity of extracranial internal carotid artery (EICA) and intraprocedural complications in patients undergoing carotid artery stenting (CAS). Methods: The study included 244 EICA in 223 patients undergoing CAS. Tortuosity in EICA was measured by the tortuosity index (TI). Multivariate logistic regression was performed to assess the independent risk factors of vasospasm during CAS. Receiver operating characteristic curve was performed to identify the cut-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…These differences were detected by analyzing three different aspects of the morphology of the collaterals: the branching pattern, tortuosity, and fractal connectivity. While, these have been previously established in the description of vascular morphology in the systemic circulation, 9,10,27,28 this is the first study to utilize all three indices in tandem to differentiate and characterize cerebrovasculature. Branching angioscore has previously been used as a marker for angiogenesis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These differences were detected by analyzing three different aspects of the morphology of the collaterals: the branching pattern, tortuosity, and fractal connectivity. While, these have been previously established in the description of vascular morphology in the systemic circulation, 9,10,27,28 this is the first study to utilize all three indices in tandem to differentiate and characterize cerebrovasculature. Branching angioscore has previously been used as a marker for angiogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…9 Tortuosity index has proven to be useful in analyzing coronary arteries to differentiate patients with chronic pressure and volume overload as well as a marker of adverse outcomes in connective tissue disorders. 10,27,28 Local connected fractal dimensions have been used previously to compare differences in retinal vasculature and differentiate oral epithelium according to degree of malignancy. 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…This leads to a higher risk of triggering embolic debris, thrombus, and dissection. In previous reports, TI was an objective method of measurement of tortuosity in carotid arteries increases the risk of neurologic complications [14,24]. A study by Faggioli et al also demonstrated that proximal TI was signifi cantly associated with both technical success and neurologic complications after CAS [14].…”
Section: Discussionmentioning
confidence: 99%
“…The free cell area is small and vessel wall support is better with closed-cell stents, causing endothelial irritation throughout the full stent length compared to hybrid-cell stents with an open-cell segment in the proximal and distal part of the stent with low radial force. A high tortuosity index, long procedural duration and female gender are independent risk factors for vasospasm during CAS [ 16 ]. However, in the current study, there was no difference in these factors between the groups.…”
Section: Discussionmentioning
confidence: 99%